Exploratory study of posterior lumbar disc herniation using low-field magnetic resonance imaging in hospital settings in Kinshasa: Case of the Diamant Medical Center - IYOTO, Djo Mbo-M.; Tshibasu, Frederick Tshienda; Yanda, Stéphane Tongo; Kinkunda, Patrick Landu; Makwanza, Lys; Nsonde, Guillain Nsiku; Ndaie, Gorbie; Nseka, Oscar Zimbuila; Kombo, joseph Kiese; Mukaya, Jean Tshibola (Orapuh Journal, 2025)
IntroductionThe limited availability of advanced medical technologies, combined with the rising prevalence of degenerative disc disease, presents a significant challenge in sub-Saharan Africa. Lumbar disc herniation requires reliable imaging for accurate diagnosis and appropriate treatment.PurposeThis study explores posterior lumbar disc herniation (LDH) using low-field magnetic resonance imaging (MRI) in hospitals in Kinshasa.MethodsA single-center, cross-sectional analytical study was conducted on 81 patients who underwent lumbar spine MRI examinations for chronic low back pain over 14 months, from December 2022 to January 2023, at the Diamant Medical Center (DMC).ResultsLumbar disc herniation was more common in men (50.6%), with the highest prevalence in the 50–65-year age group (30%). Disc desiccation was present in all segments and statistically increased with age (p < 0.05). Disc bulging was most frequently observed at L5–S1 (20% of cases), followed by disc protrusion at L4–L5 (14.8% of cases). Only disc bulging and protrusion were significantly associated with disc desiccation at L4–L5, with the latter being more than six times more likely to present with protrusion at L4–L5.ConclusionDisc desiccation remains the central feature of degenerative disc disease. More common in men, it can affect all disc segments at any age, with a higher prevalence in older adults, and can lead to disc displacement, such as bulging and protrusion, particularly in the lower lumbar spine.